MENINGKATKAN KREATIVITAS PESERTA DIDIK MELALUI PEMBELAJA-RAN SENI RUPA MENGGUNAKAN MEDIA ECOPRINT POUNDING PADA KELAS V SDN 106 PANYURAK - Irmayanti; Suherman; Muhammad Nasrul (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
improvement of students’ creativity after the implementation of the action. The study employed a mixed methods approach with Classroom Action Research (CAR) conducted in two stages involving 21 fifth-grade students of SDN 106 Panyurak. Data were collected through observation, interviews, documentation, and evaluation of students’ artworks based on aspects of originality, fluency, flexibility, and elaboration. The results showed that the implementation of ecoprint pounding media was able to improve students’ creativity. The percentage of creativity mastery in stage I reached 66.67% and increased in stage II, exceeding the success indicator of ≥80%. Therefore, ecoprint pounding media was effective in improving students’ creativity in art learning.